Macromolecular composition, productivity and dimethylsulfoniopropionate in Antarctic pelagic and sympagic microalgal communities - Sheehan, CE; Nielsen, DA; Petrou, K (INTER-RESEARCH, 2021)
© Inter-Research 2020. Microalgae form the base of the Antarctic marine food web and through their conversion of nutrients into biomass, are the principal source of energy for higher trophic levels. Environmental conditions strongly influence microalgal photophysiology, biochemistry and macromol ecular composition, which has implications for the quality and quantity of energy available for transfer through the food web. Here we assessed the photosynthetic performance, biochemical (dimethylsulfoniopropionate; DMSP) and macromolecular composition (lipids, carbohydrates and proteins) of selected diatoms sampled from 2 distinct Antarctic marine environments, namely the late spring bottom sea ice (sympagic) and near-shore ice-free coastal waters (pelagic). The photosynthetic efficiency and photoprotective capacity of the communities differed significantly, and chlorophyll a-specific gross primary productivity was 4-fold greater in the pelagic community. At the community level, pelagic microalgae had the highest DMSP content (1.4 nmol [μg chl a]-1) and the highest potential rates of DMSP lyase activity (0.87 nmol [μg chl a]-1 h-1). Comparisons within each community showed taxon-specific differences in macromolecular composition, which were strongest amongst the sympagic diatoms. Comparing across communities, pelagic diatoms had lower lipid to protein ratios, whereas sympagic diatoms were lipid rich and had significantly higher content of unsaturated fatty acids. These findings show variability in the physiology and nutritional quality of the base of the food web depending on habitat and taxonomic group and emphasise the importance of the sympagic community for providing a concentrated source of high-energy compounds during the pulsed productivity events for key grazers such as krill to survive through long dark winters.